2019
DOI: 10.1051/e3sconf/20199102019
|View full text |Cite
|
Sign up to set email alerts
|

Insulating sheath system and energy efficiency of buildings

Abstract: The article discusses the results of thermal imaging monitoring of building structures with and without insulation. Research and thermal and physical calculations showed that heat loss from the premises is determined by two groups of factors: surface loss depending on thermal conductivity, as well as vapor and air permeability of enclosing elements and heat loss at all types of joints, fasteners, etc. Thermal insulation with plate materials significantly reduces heat losses, but at the same time, heat flows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…3). It should be noted that the studies carried out at the NRU MSCU [15][16][17] showed that all insulating materials can operate at temperatures up to minus 80 °C without loss of properties and thermal insulation ability. The operating conditions of thermal insulation based on extruded polystyrene foam, polyisocyanurate foam and polyethylene foam are quite consistent with the studied ranges of operation of these materials and their operational resistance, which assumes the E3S Web of Conferences 258, 09088 (2021) UESF-2021 https://doi.org/10.1051/e3sconf/202125809088 possibility of long-term operation of the insulation system.…”
Section: Discussionmentioning
confidence: 99%
“…3). It should be noted that the studies carried out at the NRU MSCU [15][16][17] showed that all insulating materials can operate at temperatures up to minus 80 °C without loss of properties and thermal insulation ability. The operating conditions of thermal insulation based on extruded polystyrene foam, polyisocyanurate foam and polyethylene foam are quite consistent with the studied ranges of operation of these materials and their operational resistance, which assumes the E3S Web of Conferences 258, 09088 (2021) UESF-2021 https://doi.org/10.1051/e3sconf/202125809088 possibility of long-term operation of the insulation system.…”
Section: Discussionmentioning
confidence: 99%
“…3). It should be noted that the studies carried out at the NRU MSCU [15][16][17] showed that all insulating materials used can operate at temperatures up to minus 80 °C without loss of properties and thermal insulation ability. With a thickness of XPS-thermal insulation of 200 mm and a thickness of FPEinsulating coating of 20 mm, the thermal resistance of the insulating shell is not less than 4.0 m 2°С /W, and the calculated one is not less than 6.0 m 2°С /W.…”
Section: Discussionmentioning
confidence: 99%
“…3). It should be noted that the studies carried out at the NRU MSCU [15][16][17] showed that all insulating materials can operate at temperatures up to minus 80 °C without loss of properties and thermal insulation ability. possibility of long-term operation of the insulation system.…”
Section: Discussionmentioning
confidence: 99%